(untitled) (Tempo e Argumento, 2026)
This article proposes a theoretical dialogue between two current historical perspectives that focus on addressing epistemic, political, and ontological aspects of temporality and historicity. This is, on the one hand, History of the Present Time and, on the other hand, Indigenous History. The dialogue is firstly based on a series of shifts and pieces of criticism conceptualized under the notion of ‘chrono-ontology,’ and then, in a second moment, two specific inquiries on historicity in the Andean world are addressed. Finally, it thinks through the commonalities enabling a critical and productive dialogue that is useful for conceptual and political discussions on local memory from both historical perspectives.